A comparison of the persuasiveness of human and ChatGPT generated pro-vaccine messages for HPV - Dengke Xia; Dengke Xia; Mengyao Song; Mengyao Song; Tingshao Zhu; Tingshao Zhu (Frontiers in Public Health)
IntroductionPublic health messaging is crucial for promoting beneficial health outcomes, and the latest advancements in artificial intelligence offer new opportunities in this field. This study aimed to evaluate the effectiveness of ChatGPT-4 in generating pro-vaccine messages on different topics for Human Papillomavirus (HPV) vaccination.MethodsIn this study (N = 60), we examined the persuasive effect of pro-vaccine messages generated by GPT-4 and humans, which were constructed based on 17 factors impacting HPV vaccination. Paired-samples t-tests were used to compare the persuasiveness of these messages.ResultsGPT-generated messages were reported as more persuasive than human-generated messages on some influencing factors (e.g., untoward effect, stigmatized perception). Human-generated messages performed better on the message regarding convenience of vaccination.DiscussionThis study provides evidence for the viability of ChatGPT, in generating persuasive pro-vaccine messages to influence people’s vaccine attitudes. It is indicated that the feasibility and efficiency of using AI for public health communication.